1999
DOI: 10.1006/smim.1998.0158
|View full text |Cite
|
Sign up to set email alerts
|

Thymic microenvironments, 3-D versus 2-D?

Abstract: Lympho-stromal interactions in the thymus crucially determine the fate of developing T cells. Epithelial cells, interdigitating reticular cells, macrophages and fibroblasts all play a role in the shaping of the T cell repertoire. Recently published evidence shows that lympho-stromal interaction acts bi-directional. Developing T cell themselves, at different stages of differentiation, control the microarchitecture of thymic microenvironments, a phenomenon designated as ' crosstalk'. This paper reviews experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 21 publications
(21 reference statements)
0
99
0
Order By: Relevance
“…It has been previously reported that TECs from mice with early arrested T cell development present a two-dimensional structure and are unable to organize the three-dimensional structure proper of the normal thymic epithelium (63). These alterations could also explain the strong packing observed in the epithelial network of EphA4 Ϫ/Ϫ mice.…”
Section: Cd25mentioning
confidence: 98%
“…It has been previously reported that TECs from mice with early arrested T cell development present a two-dimensional structure and are unable to organize the three-dimensional structure proper of the normal thymic epithelium (63). These alterations could also explain the strong packing observed in the epithelial network of EphA4 Ϫ/Ϫ mice.…”
Section: Cd25mentioning
confidence: 98%
“…Organization and differentiation of thymic stromal cells into distinct microenvironments with a typical cellular architecture are subject to inductive signals provided by thymocytes (6,11,46). In particular, the comparison of two mouse strains, Tg⑀26 and RAG null mice, has been most informative in revealing the identity of the thymocyte subpopulation critical for the formation of a normal thymic microenvironment: TN II and/or TN III thymocytes provide signals that induce the three-dimensional organization of TEC (11).…”
Section: Induction Of a Prototypical Thymic Microenvironment Is A Prementioning
confidence: 99%
“…Notably, the organization of the thymic epithelium differs from most other epithelial organs in the body: rather than forming a sheet of cells positioned on a basement membrane, thymic epithelial cells (TEC) form a three-dimensional meshwork (6).…”
mentioning
confidence: 99%
“…However, the in vitro culture system of FTOC did not allow us to examine whether the newly generated CD4 ϩ CD8 Ϫ thymocytes could emigrate the thymus to supply CD4 T cells in the periphery. It was also unclear whether the formation of the medullary region might be affected upon the Ab treatment that restores the generation of CD4 ϩ CD8 Ϫ thymocytes, because the architecture of the thymus in the FTOC condition is severely damaged and devoid of clear cortex-medulla structure (17). have shown that the in vivo treatment with a hybrid Ab consisting of anti-V␤8 Ab and anticortical epithelial cell Ab rescues the generation of V␤8 ϩ CD4 ϩ CD8 Ϫ thymocytes in class II MHC-deficient mice.…”
Section: Ifferentiation Of Immature Cd4mentioning
confidence: 99%